Deformation Law of the Diaphragm Wall during Deep Foundation Pit Construction on Lake and Sea Soft Soil in the Yangtze River Delta - Yuan Mei; Dongbo Zhou; Xueyan Wang; Liangjie Zhao; Jinxin Shen; Shumin Zhang; Yuanying Liu (Advances in Civil Engineering)
So far, there have been a large number of diaphragm walls in the Yangtze River Delta as engineering examples of deep foundation pit maintenance structures in subway stations, but there is a lack of systematic research and summary on the deformation characteristics of ground connecting walls. This study aimed to clarify the deformation law of the diaphragm wall during the excavation of a deep foundation pit in a soft soil region. Based on the monitoring data of the diaphragm wall of the deep foundation pit of the Hangzhou metro station, the monitoring data of the deep foundation pits of 15 subway stations in Shanghai and Ningbo cities around Hangzhou were considered. Grouping and classification methods were used to analyze the similarities and differences in the deformation characteristics of the diaphragm wall in the three regions. The results indicate the following: the maximum lateral deformation of the diaphragm wall in Hangzhou increases linearly with the relative depth of the maximum lateral deformation. The maximum lateral deformation of the foundation pit in Hangzhou is 0.072% H∼0.459% H, with a mean of 0.173% H. The wall deformation in Hangzhou varies significantly with the depth of the foundation pit, but the influence of the depth of the foundation pit on the wall deformation is considerably less than that in Shanghai and Ningbo. The corresponding position of the maximum lateral deformation in the excavation depth increases linearly with the excavation depth of the foundation pit, and the corresponding position of the lateral deformation of the diaphragm wall in Shanghai is more affected by the excavation depth of the foundation pit. The lateral deformation of the diaphragm wall increases rapidly in the range of 0 H–0.5 H, and the maximum lateral deformation occurs at 0.5 H–1.1 H.